The Impact of Environmentally Friendly Technology and Renewable Energy on the Operational Efficiency of Merchant Vessels at TUKS PT. Petrokimia Gresik - Mochamad Firmawan; Nyoman Ardiana Listriawati; Ari Sriantini (Jurnal Info Sains : Informatika dan Sains, 2025)
The shipping industry faces significant challenges in reducing emissions and improving ship operational efficiency. This study aims to analyze the impact of environmentally friendly technology and renewable energy utilization on the operational efficiency of merchant vessels. The study was conducted at TUKS PT. Petrokimia Gresik using a quantitative approach by distributing questionnaires to 96 respondents, who were ship operators and technicians. Data were analyzed using multiple linear regression to test the partial and simultaneous effects of both independent variables on operational efficiency. The results of the study indicate that both environmentally friendly technology and renewable energy significantly influence ship operational efficiency, both partially and simultaneously. The coefficient of determination (R²) of 0.674 indicates that 67.4% of the variation in operational efficiency is explained by these two variables. This finding reinforces the urgency of implementing a green shipping strategy in the Indonesian maritime sector. This study suggests the need for continued investment in low-emission technologies and the use of alternative energy sources in industrial ports.